Headwaters : A Journey on Alabama Rivers - Young, Beth Maynor (Book collections on Project MUSE., 2009)
In addition to being a celebration of their richness, Headwaters serves as a call to greater stewardship of these riverine resources. Conservation sidebars describe the current efforts in this direction and encourage further study and protection. This book tells us, in glorious color and instructive word, why well always treasure these wonderful rivers.